SEPARATION AND THE POLITICS OF THEORY. - Moreiras, Alberto (Angelaki: Journal of the Theoretical Humanities, 2001)
Focuses on an operation of transcoding by setting into active equivalence the ideological code of postmodernism theory itself, and the alternative code of subalternism. Phantasmatic compatibility of subalternism and postmodernism; Exploration of the dialectical residue in the very adventure of thinking as separation; How thinking is eminently subject to primitive accumulation.